A Systematic Review of the Various Effect of Arsenic on Glutathione Synthesis In Vitro and In Vivo. (29th July 2020) - Ran, Shanshan; Liu, Jiaqing; Li, Shugang
Abstract : Background . Arsenic is a toxic metalloid widely present in nature, and arsenic poisoning in drinking water is a serious global public problem. Glutathione is an important reducing agent that inhibits arsenic-induced oxidative stress and participates in arsenic methylation metabolism. Therefore, glutathione plays an important role in regulating arsenic toxicity. In recent years, a large number of studies have shown that arsenic can regulate glutathione synthesis in many ways, but there are many contradictions in the research results. At present, the mechanism of the effect of arsenic on glutathione synthesis has not been elucidated. Objective . We will conduct a meta-analysis to illustrate the effects of arsenic on GSH synthesis precursors Glu, Cys, Gly, and rate-limiting enzyme γ -GCS in mammalian models, as well as the regulation of p38/Nrf2 of γ -GCS subunit GCLC, and further explore the molecular mechanism of arsenic affecting glutathione synthesis. Results . This meta-analysis included 30 studies in vivo and 58 studies in vitro, among which in vivo studies showed that arsenic exposure could reduce the contents of GSH (SMD = − 2.86, 95% CI (-4.45, -1.27)), Glu (SMD = − 1.11, 95% CI (-2.20, -0.02)), and Cys (SMD = − 1.48, 95% CI (-2.63, -0.33)), with no statistically significant difference in p38/Nrf2, GCLC, and GCLM. In vitro studies showed that arsenic exposure increased intracellular GSH content (SMD = 1.87, 95% CI (0.18, 3.56)) and promoted the expression of p-p38 (SMD = 4.19, 95% CI (2.34, 6.05)), Nrf2 (SMD = 4.60, 95% CI (2.34, 6.86)), and GCLC (SMD = 1.32, 95% CI (0.23, 2.41)); the p38 inhibitor inhibited the expression of Nrf2 (SMD = − 1.27, 95% CI (-2.46, -0.09)) and GCLC (SMD = − 5.37, 95% CI (-5.37, -2.20)); siNrf2 inhibited the expression of GCLC, and BSO inhibited the synthesis of GSH. There is a dose-dependent relationship between the effects of exposure on GSH in vitro . Conclusions . These indicate the difference between in vivo and in vitro studies of the effect of arsenic on glutathione synthesis. In vivo studies have shown that arsenic exposure can reduce glutamate and cysteine levels and inhibit glutathione synthesis, while in vitro studies have shown that chronic low-dose arsenic exposure can activate the p38/Nrf2 pathway, upregulate GCLC expression, and promote glutathione synthesis.